Synthesis, self-assembly and thermoresponsive behavior of Poly(lactide-co-glycolide)-b-Poly(ethylene glycol)-b-Poly(lactide-co-glycolide) copolymer in aqueous solution. (3rd May 2021) - Chang, Xiaohua; Hu, Dengwen; Chen, Liangren; Wang, Yaping; Zhu, Yutian
Abstract: Thermoresponsive block copolymer (BCP) micelles have attracted increasing attentions due to their potential in biological applications. Many studies have investigated facile strategies to tune the cloud point ( T cp ) of thermoresponsive polymer, such as changing hydrophobic/hydrophilic block ratio, micelle concentration and addition of salt. Considering the dependence of properties and functions of BCPs on thermal-induced structural transition, it is necessary to understand the universal mechanism of structural changes during temperature-induced phase transition; whereas it is challenging to achieve precise structure and properties of BCP micelles with T cp changes. Herein, we choose thermoresponsive poly (L-lactide- co -glycolide)-poly (ethylene glycol)-poly (L-lactide- co -glycolide) (PLGA-PEG-PLGA) block copolymer as a model system and utilize synchrotron-radiation small-angle X-ray scattering (SAXS) technique to systematically investigate the assembled structure of PLGA-PEG-PLGA and the mechanism for thermally induced structural transition of BCP micelle. With the increase of PLGA hydrophobic block, the T cp significantly decreases, ascribed to the enhancement of the core size, aggregation number, as well as the packing density of PLGA in micelle core. Moreover, the increase of micelle concentration and the addition of salt also decreases the T cp . Furthermore, temperature-induced drug release is also investigated, the release rate is much faster at above T cp . Graphical abstract: Image 1 Highlights: T cp of E-LG micelles can be tuned by hydrophobic/hydrophilic block ratio, micelle concentration and addition of salt. Thermally induced structural transition of E-LG micelles are analyzed by SAXS techniques. The drug release rate of E-LG micelles is much faster at above T cp .